(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Research is an important and essential part of any industry or institution. It helps in discovering new ground breaking facts about existing subjects and systems. Research is an important part of undergraduate curriculum. Objective: To understand the importance of research as a subject in hospitality under-graduate courses. Methodology: Data was collected by means of a questionnaire which was filled by the hospitality undergraduate students (n=200). Results: The findings of the study revealed that 76 % of respondents accepted that research is an important subject for undergraduate, 54% respondent accepted its benefits in skill developments. Among all respondents only 21% respondents showed interest in becoming researchers in future. Overall the students felt the importance of the subject. However, very few showed interest in pursuing research as a career. Conclusion: There is a need to sensitize students to increase the awareness and promote research not only as a subject but as a culture.